Combined Pre- and Postnatal Minimally Invasive Approach to a Complex Symptomatic Congenital Pulmonary Airway Malformation - Macchini, Francesco; Mazzoleni, Stefano; Cavallaro, Giacomo; Persico, Nicola; Borzani, Irene; Leva, Ernesto (European Journal of Pediatric Surgery Reports, 2023)
Congenital pulmonary airway malformation (CPAM) is a rare congenital lung lesion that usually remains asymptomatic during the fetal and neonatal period. However, it can occasionally cause prenatal cardiocirculatory failure and fetal hydrops, requiring a thoraco-amniotic shunt (TAS) placement. In other cases, it can also cause symptoms at birth (such as respiratory distress) and may require urgent surgical intervention. Thoracoscopic lobectomy for neonates is rarely reported. Here, we report a case of right macrocystic CPAM causing fetal hydrops at 27 weeks of gestation. The fetus was treated with a TAS placement that successfully resolved the hydrops. At 39 weeks of gestation, a male neonate was born (weight 2,850 g). The TAS spontaneously displaced during delivery, causing an open pneumothorax (PNX), initially treated with a drainage. His condition gradually worsened, requiring ventilatory support. Computed tomography (CT) scan showed different giant cysts in the context of the right lower lobe, left mediastinal shift, and compression of the rest of the lung. An urgent surgical management was required. A thoracoscopic right lower lobectomy was performed at 10 days of life (weight 2,840 g). The postoperative course was uneventful; the child remained totally asymptomatic and showed a good recovery. To the best of our knowledge, this is the first reported case of open iatrogenic PNX following TAS positioning and the second of neonatal thoracoscopic lobectomy in a newborn weighting less than 3 kg. The purpose of this report is to indicate that minimally invasive surgery is feasible, safe, and effective for the resection of CPAM, even in small newborns.
Keywords: congenital pulmonary airway malformation; thoraco-amniotic shunt; thoracoscopic lobectomy; neonate; case report